FAREWELL BEREHYNIA – LITERARY ATTEMPTS AT DEMYTHOLOGIZATION OF THE STEREOTYPICAL IMAGE OF UKRAINIAN WOMEN. SELECTED EXAMPLES OF CONTEMPORARY UKRAINIAN WOMEN’S PROSE. - Radecka, Aniela (Porównania, 2018)
The author analyses the literary treatments aimed at the demythologization of the Berehynia figure in selected novels by Oksana Zabuzhko, Sofija Andrukhovych and Natalka Sniadanko. Progressing from the nineties in a highly artistic literary discourse (and also in middle literature) the demythologization of the Berehynia figure is one of the most important elements of the process of the (re)construction of the female socio-cultural identity, as it contains the opposition of women to the existing situation.